BAHASA ARAB DAN URGENSINYA DALAM MEMAHAMI AL-QUR’AN - Intan Sari Dewi (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
Arabic has an important role in understanding the Qur’an and interpret. Arabic is the language of the Qur’an. There is a correlation between the Arabic interpretation of the Qur’an. This article will discuss a few things. First, hermeneutics as a science to explain and understand the meaning contained in the Qur’an. Second, the role of the Arabic language for understanding the Qur’an and interpret. Qur’an has a height uslub (style) and the richness of meaning.Keywords: Arabic, understanding, interpretation, Qur’an